OpinionSim: Modelling and simulating stakeholders' feedback to product-service systems - Neves-Silva, Rui (2018)
This paper describes the OpinionSim simulator developed in the scope of project DIVERSITY. DIVERSITY is related with the design of product-service systems (PSS) using real time feedback loops from internal and external stakeholders. For that purpose, the DIVERSITY platform includes Sentiment Analysis components that process posts retrieved from social media networks. Nonetheless, the test of Sentiment Analysis components requires a dataset, i.e. a set of posts, which exploit the full range of possible opinions in a controlled way. Additionally, to test the market segmentation functionalities we need to control the characteristics of the population generating the posts. The OpinionSim simulator here described meets the requirements to support the testing process.